Evaluation of Clinical and Hematological Effect of Xylazine-Ketamine and Xylazine-Atropine in Rabbit - Sah, Pradeep Kumar; Gautam, Manish; Sapkota, Swastika; Shah, Shambhu (Journal of the Institute of Agriculture and Animal Science, 2024)
This study was conducted to evaluate the clinical and hematological changes during Xylazine-Ketamine (XK) and Xylazine-atropine (XA) anesthesia in rabbits. Ten healthy and well-fed Rabbits of 1.6 to 2.0 kg BW were selected and divided into two groups: Group I (XK) and Group II (XA). Rabbits in Group I (n=5) were anesthetized with a combination of Xylazine HCl @ 5 mg/kg BW (IM) and Ketamine HCl @ 35 mg/kg BW (IM), whereas Xylazine HCl @ 5 mg/kg BW (IM) and Atropine Sulphate @ 0.2 mg/kg BW (IM) were used for anesthesia in Group II (n=5). In both groups, various clinical parameters like heart rate, respiration rate and temperature were collected from the rabbits before induction of anesthetic agents (control) and thereafter on 15, 30, 45, 60,75, and 90 minutes of post-induction and blood parameters at 0 minute and 30 minutes to evaluate hematological changes. In addition, clinical changes in temperature, respiration and heart rate were also assessed in both groups. RBC, Hb, MCV, MCH and MCHC were decreased significantly (p<0.05) in Group I(XK), temperature, respiration and heart rate were decreased significantly (p<0.05) in both groups during the experiment. There were no significant differences in lymphocytes, monocytes, granulocyte, HCT, platelets values from baseline in group I(XK) and Group II(XA). The rabbits recovered from anesthesia uneventfully. This result showed that the combination of Xylazine and Ketamine would give better anesthetic results in terms of clinical and hematological parameter and general anesthesia compare to Xylazine and Atropine in healthy rabbits. Rabbits should be carefully monitored by the veterinarians during surgical interventions to avoid anesthesia-related risks and complications.